Autocad-Based Electrical Installation Design Training to Improve the Skills of PSG Students during the Pandemic - indrawati, elsanda merita; Kartika Rahayu; M. Dewi Manikta Puspitasari; Miftakhul Maulidina; Dina Nur Anggraini (Universitas Nusantara PGRI Kediri, 2021)
Abstract— The COVID-19 pandemic has had an impact on all fields, one of which is education. The main impact in the field of education is that students have to study at home with a distance learning system. This does not reduce the emergence of companies as SMK partners in improving the skills of PSG students during the pandemic. One of the things that happened to the electrical installation contractor company, where the requirements for PSG students at the company was to have the competence to design building installations using Autocad at Canda Bhirawa Pare Vocational School, productive subjects of engineering drawing still use manual drawing systems. This is a problem for SMK because the training will not run with the existing learning system at SMK Canda Bhirawa, so with this assistance it is hoped that students' skills will increase and in accordance with the competencies desired by the company as a SMK partner. This service activity includes observation, analysis, training, monitoring and evaluation. The results of this service activity are based on observations of skill performance, namely using students' skills in drawing autocad electrical drawings.